Randomised controlled trial to evaluate the effect of foot trimming before and after first calving on subsequent lameness episodes and productivity in dairy heifers - Mahendran, S.A.; Huxley, J.N.; Chang, Y.-M.; Burnell, M.; Barrett, D.C.; Whay, H.R.; Blackmore, T.; Mason, C.S.; Bell, N.J. (Elsevier, 2017)
The objective of this study was to assess both independent and combined effects of routine foot trimming of heifers at 3 weeks pre-calving and 100 days post calving on the first lactation lameness and lactation productivity. A total of 419 pre-calving dairy heifers were recruited from one heifer rearing operation over a 10-month period. Heifers were randomly allocated into one of four foot trimming regimens; pre-calving foot trim and post-calving lameness score (Group TL), pre-calving lameness score and post-calving foot trim (Group LT), pre-calving foot trim and post-calving foot trim (Group TT), and pre-calving lameness score and post-calving lameness score (Group LL, control group). All heifers were scored for lameness at 24 biweekly time points for 1 year following calving, and first lactation milk production data were collected.